2009
DOI: 10.1017/s0022029909990276
|View full text |Cite
|
Sign up to set email alerts
|

Retinol binding protein 4 in dairy cows: its presence in colostrum and alteration in plasma during fasting, inflammation, and the peripartum period

Abstract: Retinol-binding protein 4 (RBP4) is a plasma protein involved in retinol transportation, and recent evidence in rodents suggests that RBP4 is also a metabolic regulator that modifies insulin sensitivity. To assess how RBP4 levels are regulated in ruminants, we determined the RBP4 concentrations in bovine plasma and milk using Western blot analysis. Plasma RBP4 levels in non-pregnant non-lactating (control) cows were around 45 mg/ml, which were sustained during 60-h fasting, but decreased significantly 4 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
(58 reference statements)
4
18
2
Order By: Relevance
“…We did not find any time-or treatment-related differences in the mRNA expression of RBP4 during the course of the study. Recent studies by Abd Eldaim et al (1) and Rezamand et al (39) report fluctuation in the plasma RBP4 concentration during the transition period, with a sharp decline immediately after parturition and rebound toward prepartum levels in early lactation. Our findings are in contrast to the findings of Rezamand et al (39), who observed that physiological state affected hepatic RBP4 expression during the periparturient period.…”
Section: Discussionmentioning
confidence: 96%
“…We did not find any time-or treatment-related differences in the mRNA expression of RBP4 during the course of the study. Recent studies by Abd Eldaim et al (1) and Rezamand et al (39) report fluctuation in the plasma RBP4 concentration during the transition period, with a sharp decline immediately after parturition and rebound toward prepartum levels in early lactation. Our findings are in contrast to the findings of Rezamand et al (39), who observed that physiological state affected hepatic RBP4 expression during the periparturient period.…”
Section: Discussionmentioning
confidence: 96%
“…Retinol concentration typically decreases around parturition due in part to the transfer of retinol and its derivatives into colostrum [ 37 ] and also because of the inflammation during this period [ 38 ]. Retinol is stored in the liver, and its transport to target tissues depends on retinol binding protein 4 ( RBP4 ) [ 39 ]. As RBP4 is Zn-dependent [ 40 ] the decrease in plasma retinol during the transition period may be partly associated with a direct (diet) or indirect (immune response) [ 41 ] Zn deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Abd Eldaim et al (2010) also reported that plasma RBP4 decreased immediately after parturition and returned to prepartum levels by 2 wk postpartum. The decline in plasma RBP4 can be attributed to its flux toward the mammary gland immediately after calving, although several factors, including inflammatory reactions and protein intake, may affect RBP4 synthesis.…”
Section: Effect Of Overfeeding On Hepatic Gene Expressionmentioning
confidence: 92%